Facile Two-Step Synthesis of Methyl Bis(2,2,2-trifluoroethyl)phosphonoacetate by Exploiting Garegg–Samuelsson Reaction Conditions - Sano, Shigeki; Matsumoto, Tomoya; Toguchi, Munehisa; Nakao, Michiyasu (Synlett, 2018)
A facile two-step synthesis of methyl bis(2,2,2-trifluoroethyl)phosphonoacetate (Still–Gennari reagent) has been developed by exploiting Garegg–Samuelsson reaction conditions. Starting from trimethyl phosphonoacetate, Still–Gennari reagent was prepared in 94% yield via methyl 2-{bis[(trimethylsilyl)oxy]phosphoryl}acetate intermediate. This synthetic procedure was also used to prepare some kinds of Horner–Wadsworth–Emmons reagents and related compounds.
Keywords: Horner–Wadsworth–Emmons reagents; Still–Gennari reagent; phosphorus; Garegg–Samuelsson reaction conditions; 2,2,2-trifluoroethanol